Intersectional realities: Addressing the gaps in equity infrastructure to include racialized international students at a Canadian university - Arumuhathas, Shamiga (Journal of International Students, 2026)
This research investigates the intersectional realities of racialized international students at a Canadian university, exposing significant deficiencies in the institution’s equity, diversity, inclusion, and decolonization (EDID) policies. Utilizing a heuristic case study approach, it reveals experiences of social segregation and cultural essentialization, often within a Euro-Western context. By applying Critical Race Theory (CRT), the study uncovers systemic barriers that exacerbate marginalization, demonstrating how institutional practices often fail to align with the commitment to inclusivity. Participants exhibit remarkable resilience, advocating for a true alignment between policies and the complexities of their experiences. The findings call for a transformation in EDID initiatives to ensure authentic belonging and equity within Canadian higher education.